Access fees for competing lobbies - Martin Gregor (Charles University in Prague, Institute of Economic Studies (IES), 2014)
We model 'money buys access' informational lobbying as a commitment from the policy-maker to observe a lobby's verifiable evidence only upon receiving an access fee. We specifically examine the policy-maker's optimal access fees in the presence of two strictly competing lobbies. Our novel method constructs bargaining surpluses in parallel bilateral bargaining problems in which a negative sign for the bilateral surplus implies a strategic access restriction. This approach easily identifies the equilibrium set of participating lobbies for any information structure and any timing for the lobbies' access. We explain the incomplete participation of lobbies and the resulting information and welfare distortion using the information and revenue complementarities of signals. We also show that a lower bias may be either a blessing or curse for a lobby depending on the information structure and timing. Finally, we demonstrate that promoting lobbying competition may be detrimental to welfare due to the policy-maker's revenue-information tradeoff.
Keywords: C72; C78; D72; D83; 330; informational lobbying; access fee; persuasion; verifiable evidence